IMPLEMENTASI RENCANA KERJA PERKANTORAN DI YAYASAN AZ-ZIKRA SENTUL BOGOR - Yulia Andriani; Muhammad Hidayat Ginanjar; Muslim Muslim; Heriyansyah Heriyansyah (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2019)
This research was conducted with the aim of knowing how to implement the Office Plan Work Plan (RKP) at the Az-Zikra Sentul Foundation. The focus of this study is related to the office work plan with three subfocuses, namely (1) what is the mechanism for preparing the RKP by Aaz-Zikra, (2) what are the types of plans made, and (3) which types of plans have been realized. This study uses a qualitative research approach and descriptive method. Data collection techniques carried out in qualitative research are in-depth interviews where in this study the researcher himself is the main instrument for finding data by interacting symbolically with the informants studied. The findings obtained at the Az-Zikra Foundation related to the implementation of the RKP are: (1) The program planning mechanism at the foundation was initiated by K.H. Muhammad Arifin Ilham who now serves as Chair of the Board of Trustees. Starting from the habit of dhikr in mosques to the famous abroad until finally having a dzikir mosque funded by the Libyan government until now it is able to stand up to fund the foundation program independently. (2) There are four types of planning based on organizational goals made by the management of the Az-Zikra Foundation. (3) Which can be said to be realized by the Az-Zikra Sentul Foundation, starting from strategic planning, tactical planning, operational planning and situational planning.Keywords: implementation, work plan, office.